Airborne eDNA Reflects Human Activity and Seasonal Changes on a Landscape Scale - Johnson, Mark D.; Cox, Robert D.; Grisham, Blake A.; Lucia, Duane; Barnes, Matthew A. (Frontiers in Environmental Science, 2021)
Recent research on environmental DNA (eDNA), genetic material shed by organisms into their environment that can be used for sensitive and species-specific detection, has focused on the ability to collect airborne eDNA released by plants and carried by the wind for use in plant community analysis, including detection of invasive and endangered species. Another possible application of airborne eDNA is to detect changes in plant communities in response to activity or changes on a landscape-scale. Therefore, the goal of this study was to demonstrate how honey mesquite, blue grama, and general plant airborne eDNA changes in response to human activity on a landscape-scale. We monitored airborne eDNA before, during, and after a rangeland restoration effort that included honey mesquite removal. As expected, restoration activity resulted in a massive increase in airborne honey mesquite eDNA. However, we also observed changes in abundance of airborne eDNA from the grass blue grama, which was not directly associated with the restoration project, and we attribute these changes to both human activity and seasonal trends. Overall, we demonstrate for the first time that activity and changes on a landscape-scale can be tracked using airborne eDNA collection, and we suggest that airborne eDNA has the potential to help monitor and assess ecological restoration projects, track changes due to global warming, or investigate community changes in response to encroachment by invasive species or extirpation of threatened and endangered species.